2018
DOI: 10.1097/hcr.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Using 6-Min Walk Distance Expressed as a Percentage of Reference to Evaluate the Effect of Pulmonary Rehabilitation in Elderly Patients With Interstitial Lung Disease

Abstract: PR had a beneficial effect on elderly patients with ILD in terms of exercise endurance. %6MWD might be more useful than the absolute 6MWD as an outcome measure of PR and as a predictor of response to PR in elderly patients with ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
8
0
5
Order By: Relevance
“…Eligible patients were recruited from IPF patients as a subgroup of patients recruited for the Toho Rehabilitation for Interstitial Pneumonia (TRIP) study from July 2014 to July 2017. The TRIP study is investigating the long-term effects (2 years of follow-up) of pulmonary rehabilitation on patients with chronic interstitial lung diseases due to any cause, and is still ongoing at Toho University Omori Medical Center, Tokyo, Japan (Igarashi et al 2018). The Toho University Omori Medical Center Ethics Committee approved the study (approval #27-82).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eligible patients were recruited from IPF patients as a subgroup of patients recruited for the Toho Rehabilitation for Interstitial Pneumonia (TRIP) study from July 2014 to July 2017. The TRIP study is investigating the long-term effects (2 years of follow-up) of pulmonary rehabilitation on patients with chronic interstitial lung diseases due to any cause, and is still ongoing at Toho University Omori Medical Center, Tokyo, Japan (Igarashi et al 2018). The Toho University Omori Medical Center Ethics Committee approved the study (approval #27-82).…”
Section: Subjectsmentioning
confidence: 99%
“…Leg muscle strength was assessed as quadriceps muscle force estimated by measuring isometric knee extension strength with a hand-held dynamometer (a Mobie; Sakai Medical Corp., Tokyo, Japan). Patients sat on a training bench and adjusted the position of the gluteal region so that a bench leg was behind the lower extremity on the measurement side (Igarashi et al 2018).…”
Section: Physical Performance Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in patients with ILD reported 10 different exclusion criteria (Figure 4). From these, unstable cardiovascular disease [198,199,202,203,208,209] ( n = 6; 37.5%) was the most reported criterion, followed by contraindications to exercise training and/or testing (e.g., unstable angina, recent myocardial infarction or cerebrovascular accident) [201,204,207] ( n = 3; 18.8%). Four (25.0%) studies [185,197,205,206] did not report any information about exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In Studien mit Patienten mit ILD waren 10 verschiedene Ausschlusskriterien angegeben (Abb 4). Von diesen waren instabile kardiovaskuläre Erkrankungen [198, 199, 202, 203, 208, 209] (n = 6; 37,5%) das am häufigsten berichtete Kriterium gefolgt von Kontraindikationen für Bewegungstraining und/oder Belastungstests (z.B. instabile Angina, kürzlich stattgehabter Myokardinfarkt oder zerebrovaskuläres Ereignis) [201, 204, 207] (n = 3; 18,8%).…”
Section: Ergebnisseunclassified